2015
DOI: 10.1177/1088357615588516
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ Experience of an Asperger Syndrome Diagnosis

Abstract: This study explores the impact on 74 adults attending an Asperger syndrome diagnosis clinic. Feedback forms containing quantitative and qualitative measures were completed 3 months post-assessment. Qualitative responses were analyzed using thematic content analysis. Regarding questions about their emotional response, participants reported themes of “Relief,” “Feeling better about self,” “Mixed feelings,” “No clear feelings,” and “Negative feelings.” Regarding the impact of the diagnosis on their lives, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…Previous qualitative and quantitative studies of adults' experiences of being diagnosed with autism also report relief as a predominant emotional response, and that the diagnosis offered an explanation for their experiences of life. 84,[89][90][91][92] They too describe the potential range of emotions, both positive and negative, which may be experienced. 79,91,93,94 Similarly, they also report how the diagnosis may facilitate improvements in family relationships and the support received from other services or educational establishments/the workplace.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Previous qualitative and quantitative studies of adults' experiences of being diagnosed with autism also report relief as a predominant emotional response, and that the diagnosis offered an explanation for their experiences of life. 84,[89][90][91][92] They too describe the potential range of emotions, both positive and negative, which may be experienced. 79,91,93,94 Similarly, they also report how the diagnosis may facilitate improvements in family relationships and the support received from other services or educational establishments/the workplace.…”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Despite the large burden of depression in this population, few studies have attempted to establish the psychometric properties of common depression symptom measures in adults with ASD (for a review, see Cassidy, Bradley, Bowen, et al, 2018). Studies measuring depression in ASD have previously used a number of measures validated in the general population, including the Beck Depression Inventory-Second Edition (BDI-II; Moss et al, 2015), Depression Anxiety Stress Scales (Maddox & White, 2015;Nah et al, 2018), Hamilton Depression Rating Scale (Buchsbaum et al, 2001), Hospital Anxiety and Depression Scale (Powell & Acker, 2014), Montgomery-Åsberg Depression Rating Scale (Wentz et al, 2012), and Patient Health Questionnaire-9 (PHQ-9; Hedley et al, 2018) without assessing the validity of those measures in ASD. In recent years, several studies have attempted to fill this gap, reporting psychometric properties of the BDI-II (Gotham et al, 2015), Hospital Anxiety and Depression Scale (Uljarević et al, 2018), and PHQ-9 (Arnold et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was no significant association between participants who believed that the AC diagnostic disclosure made them more helpful compared to whether they were actually helpful during the game. These findings help to explain why diagnostic disclosure, despite enhancing social perceptions by others, can still result in negative discrimination in terms of behavior as reported by autistic people themselves (Davidson and Henderson, 2010; Powell and Acker, 2016; Treweek et al, 2018).…”
Section: Discussionmentioning
confidence: 74%
“…To date a number of studies have explored how autistic expressions and behavior are perceived by non-autistic people through vignettes and thin-slice judgements (e.g., utilizing video, image, and audio), showing that disclosing a diagnosis of autism significantly improves evaluations (e.g., Chambres et al, 2008; Faso et al, 2014; Brosnan and Mills, 2016). However, reports from autistic people indicate that disclosure of a diagnosis can also result in stigma and negative discrimination (Davidson and Henderson, 2010; Powell and Acker, 2016; Treweek et al, 2018), resulting in a gap in the literature in connecting self-reported perceptions with actual behavior.…”
Section: Introductionmentioning
confidence: 99%